CRISPR/Cas9-Mediated α-ENaC Knockout in a Murine Pancreatic β-Cell Line - Zhang, Xue; Zhao, Lihua; Jin, Runbing; Li, Min; Li, Mei-Shuang; Li, Rongfeng; Liang, Xiubin (Frontiers in Genetics, 2021)
Many ion channels participate in controlling insulin synthesis and secretion of pancreatic β-cells. Epithelial sodium channel (ENaC) expressed in human pancreatic tissue, but the biological role of ENaC in pancreatic β-cells is still unclear. Here we applied the CRISPR/Cas9 gene editing technique to knockout a-ENaC gene in a murine pancreatic β-cell line (MIN6 cell). Four single-guide RNA (sgRNA) sites were designed for the exons of a-ENaC. The sgRNA1 and sgRNA3 with the higher activity were constructed and co-transfected into MIN6 cells. Through processing a series of experiment flow included drug screening, cloning and sequencing, the a-ENaC gene-knockout in MIN6 cells (a-ENaC-/-) were obtained. Compared with the wild type MIN6 cells, the cell viability and insulin content were significantly increased in a-ENaC-/- MIN6 cells. Therefore, a-ENaC-/- MIN6 cells generated by CRISPR/Cas9 technology added an effective tool to study the biological function of a-ENaC in pancreatic β-cells.